2020
DOI: 10.29328/journal.jnnd.1001035
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system diseases associated with blood brain barrier breakdown - A Comprehensive update of existing literatures

Abstract: Blood vessels that supply and feed the central nervous system (CNS) possess unique and exclusive properties, named as blood–brain barrier (BBB). It is responsible for tight regulation of the movement of ions, molecules, and cells between the blood and the brain thereby maintaining controlled chemical composition of the neuronal milieu required for appropriate functioning. It also protects the neural tissue from toxic plasma components, blood cells and pathogens from entering the brain. In this review the impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 130 publications
0
4
0
5
Order By: Relevance
“…The authors reported increase in blood density, reduction in blood vessel diameter and BBB leakage in both the mice model and HD patients [40]. Some other studies also reported about the evidence BBB disruption in HD [41][42][43][44]. Amyotrophic lateral sclerosis: Animal model studies have reported previously about the occurrence blood spinal cord barrier breakdown before motor neuron injury [45][46][47][48][49].…”
Section: Hunting Ton's Diseasementioning
confidence: 93%
See 3 more Smart Citations
“…The authors reported increase in blood density, reduction in blood vessel diameter and BBB leakage in both the mice model and HD patients [40]. Some other studies also reported about the evidence BBB disruption in HD [41][42][43][44]. Amyotrophic lateral sclerosis: Animal model studies have reported previously about the occurrence blood spinal cord barrier breakdown before motor neuron injury [45][46][47][48][49].…”
Section: Hunting Ton's Diseasementioning
confidence: 93%
“…HIV-Assoc iated Neurocognitive Disorder: HIV-1positive individuals today still develop HIV-1-ass ociated dementia (HAD) and neurocognitive impairment in spite of good prognosis with antiretroviral therapy [76,77]. Imbalances between MMPs and TIMPs are involved in BBB disruption and are implicated in the pathogenesis of HAND in H IV-1 patients [78].…”
Section: Other Chronic Neurodegenerative Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…To increase the effectiveness of therapy, it is advisable to combine neuropetides with antioxidants and antihypoxants, choline precursor drugs. В ЦНС различают 4 типа нейроглиальных клеток: астроциты, микроглиальные клетки, олигодендроциты и эпендимальные клетки [10]. Активация астроцитов при любой ишемии ускоряет процессы нейродегенерации и увеличивает зону повреждения гиппокампа, формирования глиальных рубцов с ингибирующим аксональным действием.…”
Section: иерархия патогенетических механизмов и клинических проявлени...unclassified